Demokrasi Lokal dalam Bingkai Pilkada di Aceh Pasca MoU Helsinki - Agus Junaidi; Ruhdiara Ruhdiara; Siti Fatimah (Prodi Sosiologi FISIP Universitas Teuku Umar, 2022)
Pilkada is a political competition in society and has built awareness about the rational use of voting rights, because voters are often influenced by other considerations such as personal proximity, kinship, ethnicity and so on. This is what is then ridden as one that causes conflict. Moreover, Aceh is a province with a special legal community unit which is contained in Law No. 11 of 2006 concerning the Government of Aceh. One thing that is special is the political problem, where Aceh has a specialty in regulating its own politics and Aceh also has local parties that can participate in election contestations in Aceh. The purpose of this study is to find out how the political contestation in Aceh after Mou Helsinki in the 2006 Pilkada, 2012 Pilkada, and 2017 Pilkada. In this study the author uses a research method conducted by literature study. by collecting a number of recorded events and then analyzing them to provide a general narrative according to the phenomena found. The results showed that the Acehnese people at the beginning of the post-MoU election in Helsinki were very interested in the existence of local parties, but lately the Acehnese people have seen more of the characters than the party.